2011
DOI: 10.1159/000323317
|View full text |Cite
|
Sign up to set email alerts
|

Does the Clock Drawing Test Predict Dementia? Results of the Leipzig Longitudinal Study of the Aged (LEILA 75+)

Abstract: Background/Aims: Conversion rates to dementia are known to be high for patients with mild cognitive impairment (MCI), but the diagnosis of MCI is very time-consuming. Since the Clock Drawing Test (CDT) is quick to administer, it will be of interest to compare the predictive validity of the CDT and of an MCI diagnosis for the diagnosis of dementia. Methods: In a sample of 384 individuals, CDT scores and the presence of MCI were assessed at baseline and then compared between individuals with an incident dementia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 77 publications
(62 reference statements)
0
13
0
Order By: Relevance
“…13 new study populations[ 7 20 ] have been used to create risk models compared to the first review (all literature till 2009)[ 1 ]. There was however some overlap including use of data from the Cardiovascular Health Cognition Study[ 20 , 21 ], Leipzig Longitudinal Study of the Aged (LEILA 75+)[ 22 ], Einstein Aging Study[ 23 ], Vienna TransDanube Aging[ 24 ], Canadian Study of Health and Aging[ 25 ] and the Kungsholmen Project[ 4 ]. Sample sizes ranged from 194[ 11 ] to 29,961[ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 new study populations[ 7 20 ] have been used to create risk models compared to the first review (all literature till 2009)[ 1 ]. There was however some overlap including use of data from the Cardiovascular Health Cognition Study[ 20 , 21 ], Leipzig Longitudinal Study of the Aged (LEILA 75+)[ 22 ], Einstein Aging Study[ 23 ], Vienna TransDanube Aging[ 24 ], Canadian Study of Health and Aging[ 25 ] and the Kungsholmen Project[ 4 ]. Sample sizes ranged from 194[ 11 ] to 29,961[ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sample sizes ranged from 194[ 11 ] to 29,961[ 13 ]. Follow-up duration ranged from 1.4[ 22 ] to 20 years[ 7 ]. Follow-up rate ranged from 66%[ 12 ] to 86%[ 19 ], with 10 studies[ 4 , 7 , 11 , 14 , 15 , 17 , 20 , 21 , 23 , 25 ] not reporting attrition or dropout.…”
Section: Resultsmentioning
confidence: 99%
“…Our results were obtained in a clinic setting, so the results may not generalize to community-based populations. Recent work by others has sought to use information obtained from the MMSE or from the Clock Drawing Test to predict conversion to dementia in population-based samples, with modest success to date in terms of diagnostic accuracy (∼70%) [58,59]. In a community-based study of incident dementia cases, predictors of cognitive decline were found to differ from those identified in similarly-aged control cases [60].…”
Section: Discussionmentioning
confidence: 99%
“…Ehreke et al [24] claimed that the CDT does not exhibit sufficient quality to screen for MCI. Nevertheless, in a later publication, these authors recommended it as a possible predictive test for dementia [25]. A validation study of Cognistat concluded that this tool has moderate validity in the detection of MCI and mild dementia but that, on its own, it is not sufficient for diagnosing MCI or mild dementia [26].…”
Section: Discussionmentioning
confidence: 99%